A new coccidian parasite of the boodie, Bettongia lesueur (Mammalia: Marsupialia: Potoroidae), from Australia - Hulst, Frances; Kemp, Leah F; Slapeta, Jan (Folia parasitologica, 2016)
Four of 28 wild boodies or burrowing bettongs, Bettongia lesueur (Quoy et Gaimard) passed oocysts of species of Eimeria Schneider, 1875. The boodies are surviving on off-shore islands and in large predator-proof sanctuaries on the mainland where they were reintroduced. The boodie is a potoroid marsupial extinct from the mainland of Australia due to predation from red foxes and feral cats. Comparison with other species of the genus Eimeria indicates that the coccidium found represents a new species. Sporulated oocyst of Eimeria burdi sp. n. are pyriform, 21.0-24.0 µm (mean 22.6 µm) by 14.0-16.0 µm (14.9 µm), with a length/width ratio 1.31-1.71 (1.52) and 1-µm-thick yellowish bilayered wall. Micropyle is present at the thinner apex end filled with hyaline body. Polar granules are absent. Sporocysts are ellipsoidal, 10.0-13.5 µm (11.8 µm) by 7.0-8.5 µm (7.4 µm), shape index is 1.42-1.89 (1.63) and a very thin, poorly defined unilayered sporocyst wall is 0.2 µm thick with a domelike almost indistinct Stieda body. Substieda body is indistinct.
Keywords: Animals; bettongs; feces; Feces; taxonomy; Coccidia; druhová specificita; Australia; oocysty; Oocysts; Eimeria; Potoroidae; Species Specificity; kokcidióza; Coccidiosis; Austrálie; morphology; marsupials; Apicomplexa; zvířata; new species